Influência do estado de maturação na qualidade de cereja ‘Sweetheart’ - Ricardo-Rodrigues, S. (2022)
The cherry is highly appreciated for its organoleptic and nutritional qualities, and for its important role in disease prevention. The correct definition of the ripeness at harvest is indispensable for placing the cherry on the market with high quality. Early harvesting, either for fear of rain or for immediate economic return, often occurs especially at the beginning of the campaign. This study aims to evaluate the quality of ‘Sweetheart’ cherries at three stages of ripeness (early ripeness, commercial ripeness, and advanced ripeness), to assist the producer in defining the ideal time to harvest so that the fruit reaches the market with high quality. The results obtained suggest that the ‘Sweetheart’ cherry, at commercial ripeness, reaches values of firmness, soluble solids and acidity acceptable to the consumer. However, cherries fully ripened on the tree show better nutritional quality, with higher values of antioxidant activity, and phenolic compounds. For consumers to have cherries with high nutritional and sensory quality, the producer must determine the optimal cherry harvest stage, to minimise quality losses and dispose of production quickly and in good conditions, reducing waste.